Responsi Siswa Terhadap E-Modul Biologi Terintegrasi Nilai-Nilai Imtaq Pada Materi Otot - Husna Auliya; Siti Robiah (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This study aims to determine students' responses to the Biology E-Module integrated with Imtaq values ​​in the Muscle material that was developed. This study is a development study using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This study is limited to the development stage. Determination of the sample using purposive sampling techniques, and the number of samples is 30 students from each of 10 schools, namely SMAN 3 Teluk Meranti, SMAN 1 Pelalawan, and SMA PGRI Pekanbaru. Data collection using student response sheets, Data analysis techniques using descriptive techniques. The results of the study obtained an average student response from three schools of 91.55% (very good category).